Polybutadiene latex and electroplating ABS (Acrylonitrile Butadiene Styrene) resin prepared from same

By controlling the gel ratio and crosslinking degree of polybutadiene latex, the problem of plating binding force fluctuations in the ABS resin electroplating process is solved, and the consistency of high plating binding force and surface roughness in a wider range is achieved, improving the The overall performance of electroplating ABS.

CN119143908APending Publication Date: 2024-12-17WANHUA CHEM GRP CO LTD

Patent Information

Application Number
CN202411284370.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-13
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

The existing ABS resin electroplating process fluctuates greatly under different processing conditions, resulting in unstable resin plating bonding force and affecting the electroplating effect.

Method used

By improving the preparation method of polybutadiene latex, the latex gel rate is controlled within the range of 85%-95%, the cross-linking degree of polybutadiene latex is improved, and the morphological consistency of rubber particles is maintained during the electroplating process. Ensure the resin coating bonding force.

Benefits of technology

The resin coating bonding force is improved under wider processing conditions, ensuring the consistency of surface roughness and the integrity of the plating anchor point of the electroplated ABS, and significantly improving the coating bonding force.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119143908A_ABST
    Figure CN119143908A_ABST
Patent Text Reader

Abstract

The invention discloses polybutadiene latex and electroplating ABS (Acrylonitrile Butadiene Styrene) resin prepared from the same. According to the method, the gel rate of the latex is increased by heat treatment of the polybutadiene latex emulsion, and the latex with the gel rate increased to 85-95% is obtained, so that the latex has a better particle morphology maintaining effect under wider processing conditions. When the polybutadiene latex is used for further preparing electroplated ABS resin, a more consistent coarsening effect is achieved during electroplating and etching, and the prepared electroplated ABS resin has higher plating binding force under wider processing conditions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of ABS resin materials, and in particular relates to a polybutadiene latex and an electroplated ABS resin prepared therefrom. Background Art

[0002] ABS (Acrylonitrile-Butadiene-Styrene) resin is a two-phase polymer, which is obtained by bulk polymerization / emulsion graft polymerization. The polybutadiene rubber particles uniformly dispersed in the continuous phase SAN are used to toughen the matrix SAN.

[0003] Because it is a two-phase polymer, the dispersed phase polybutadiene rubber particles and the continuous phase SAN have different chemical properties; using this property, the surface of ABS resin can be easily modified. For example, the industry generally adopts the "degreasing-roughening-sensitization-activation-chemical plating-electroplating" method to build a metal layer on the resin surface. Since the rubber phase is etched away by chemical reagents during the roughening process, a metal-resin connection microstructure is formed in situ on the etched rubber particles during the subsequent chemical plating-electroplating process. Due to the "anchor effect" of this structure, the electroplated device prepared by this process has excellent plating bonding. This is also the fundamental reason why ABS resin and its alloys occupy 90% of the non-metallic electroplating material market (Modern Electroplating Handbook P421, Liu Renzhi, Chemical Industry Press, 2010.5).

[0004] The bonding strength of the coating is the most critical technical indicator in ABS electroplating, which affects the plating effect of the substrate and the surface performance of the finished product. In practical applications, there are many factors that affect the bonding strength of the ABS resin coating. For example, the rubber phase content, particle morphology, and acrylonitrile content in the ABS resin have a significant effect on the surface roughness effect of the roughening process, which will cause changes in the bonding strength of the resin coating. In addition, inappropriate selection of resin processing parameters (such as mold structure, injection pressure-molding temperature, resin moisture content, etc.) will also lead to local stress concentration and reduce the bonding strength of the resin coating. Processing additives (such as release agents) may also cause resin surface contamination, thereby affecting electroplating etching and further affecting the bonding strength of the coating.

[0005] Therefore, it is necessary to find a method to ensure process production efficiency and stable product performance while giving ABS resin the effect of maintaining the same shape within a wider range of processing conditions, thereby improving the bonding strength of the resin coating. Summary of the invention

[0006] In view of the above problems existing in the prior art, one of the objects of the present invention is to provide a method for preparing polybutadiene latex. By improving the preparation process, latex with rubber particles that are not easily deformed can be conveniently and efficiently prepared, thereby providing a basic polybutadiene latex for obtaining ABS resin with a wider range of processing conditions.

[0007] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention is as follows:

[0008] A method for preparing polybutadiene latex, the method comprising the following steps:

[0009] S1: adding water, emulsifier, butadiene, electrolyte, chain transfer agent and initiator into a reactor to carry out emulsion polymerization;

[0010] S2: When the polymerization reaction reaches the target conversion rate, unreacted butadiene is removed to obtain polybutadiene latex;

[0011] S3: heat-treating the polybutadiene latex emulsion to increase the gel fraction of the latex and obtain the target polybutadiene latex emulsion;

[0012] Among them, the latex gel rate in S3 is increased to 85%-95%.

[0013] When the inventors studied the problem of large fluctuations in the electroplating bonding strength index of ABS resin under different processing conditions, they surprisingly found that there is a specific relationship between the gel rate of polybutadiene latex and the injection molding deformation and the electroplating effect.

[0014] The industry has tried many methods to improve the coating adhesion and plating effect of the substrate resin. For example, patents CN103342864A, CN111372990A, and CN102653582A all proposed using a double rubber particle process to improve the coating adhesion index. However, the above process schemes all ignore the fact that particles also deform "from spherical to ellipsoidal" during the process of being processed into plastic parts. When the processing conditions change, the rubber particles will change their shape due to different shear strengths, affecting the roughness of the resin surface during the subsequent roughening process and thus affecting the resin coating adhesion.

[0015] The inventors found that when the gel rate of the intermediate polybutadiene latex is in the range of 85%-95%, its subsequent application in roughening-chemical plating-electroplating is significantly improved. Further research shows that the reason is that under this specific gel rate indicator, the particle morphology of the prepared electroplated ABS is minimally affected by injection molding shear deformation during processing, and the surface roughness consistency after resin roughening is maintained to the greatest extent, thereby improving the electroplating effect of the matrix resin and improving the bonding strength of the resin coating.

[0016] In one embodiment of the present invention, the mass ratio of each component used in the polybutadiene latex described in S1 is as follows:

[0017]

[0018] Preferably, the emulsifier is selected from C12-C20 carboxylates and / or sulfonates, preferably one or more of potassium or sodium salts of disproportionated rosin acid, oleic acid, linoleic acid, stearic acid, and dodecylbenzene sulfonic acid; preferably, the electrolyte is selected from metal salts of IA main group metals, preferably one or more of sodium carbonate, potassium carbonate, potassium phosphate, and sodium sulfite; preferably, the chain transfer agent is selected from C8-C18 mercaptans, preferably one or more of tert-dodecyl mercaptan, n-dodecyl mercaptan, n-octyl mercaptan, and n-octadecyl mercaptan; preferably, the initiator is selected from persulfate and / or organic peroxide, preferably one or more of sodium persulfate, potassium persulfate, cumene hydroperoxide, and tert-butyl hydroperoxide. The above raw materials are conventional raw material selections in this field.

[0019] In one embodiment of the present invention, the polymerization temperature in S1 is 50°C-85°C, preferably 60°C-75°C.

[0020] In one embodiment of the present invention, the particle size of the polybutadiene latex prepared in S1 is 100-500 nm, preferably 200-400 nm.

[0021] In one embodiment of the present invention, the method for removing unreacted butadiene in S2 may be flash distillation and / or stripping. The method for removing unreacted butadiene is a conventional method in the art.

[0022] In one embodiment of the present invention, in S2, when the butadiene conversion rate of the polymerization reaction reaches 85-97%, preferably 90-95%, unreacted butadiene is removed; preferably, the unreacted butadiene is removed to a mass content of <2000 ppm.

[0023] In one embodiment of the present invention, the temperature of the heat treatment in S3 is 50-90°C, preferably 60-80°C.

[0024] Another object of the present invention is to provide a polybutadiene latex.

[0025] A polybutadiene latex is prepared by the above method, and the gel fraction of the latex is 85%-95%.

[0026] Another object of the present invention is to provide a use of polybutadiene latex.

[0027] A use of polybutadiene latex, wherein the latex is prepared by the above method, or is the above polybutadiene latex, and the polybutadiene latex is used to prepare ABS resin.

[0028] Another object of the present invention is to provide an ABS resin. The finished resin has better surface roughness during electroplating and etching, and the prepared electroplated ABS has better plating bonding strength under wider processing conditions.

[0029] An ABS resin, wherein the raw material of the resin is the polybutadiene latex prepared by the above method, or the raw material of the resin is the above polybutadiene latex.

[0030] Another object of the present invention is to provide a use of ABS resin.

[0031] A use of ABS resin, wherein the raw material of the resin is the polybutadiene latex prepared by the above method, or the raw material of the resin is the above polybutadiene latex, and the ABS resin is used for electroplating ABS resin.

[0032] In some preferred examples of the present invention, the electroplated ABS resin is prepared by further emulsion graft polymerization, coagulation, and drying of the polybutadiene latex to form ABS graft powder, and then blending with SAN resin (styrene-acrylonitrile copolymer). The preparation of ABS graft powder is a conventional method in the art.

[0033] In some preferred examples of the present invention, the electroplated ABS resin has a coating bonding strength of >9N / cm, such as 9N / cm, 10N / cm, 12N / cm, and 14N / cm, at an injection molding rate of 5-50ccm / s.

[0034] The electroplated ABS resin of the present invention is further prepared by using the above-mentioned polybutadiene latex. There is no special requirement for the preparation method. The technicians can refer to the existing technology and combine and screen the steps and parameters according to actual needs to prepare the resin.

[0035] Compared with the prior art, the present invention has the following beneficial effects:

[0036] The invention improves the crosslinking degree of polybutadiene in latex particles by heat-treating the polybutadiene latex prepared by the reaction. In particular, it is found that when the gel fraction is controlled within the range of 85%-95%, after further preparing the electroplated ABS resin, the rubber particles have a better effect of maintaining the morphology in a wider processing window (under an injection molding rate of 5ccm / s-30ccm / s), thereby improving the integrity of the coating anchor points formed by resin roughening etching, so that the prepared ABS resin has a consistent electroplating bonding force of more than 9N / cm under the above processing window. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 This is an electron microscope photo of the electroplated ABS prepared in Example 1;

[0038] Figure 2 This is an electron microscope photograph of the electroplated ABS prepared in Comparative Example 1. DETAILED DESCRIPTION

[0039] The present invention is further described below by way of examples and comparative examples, however, the examples do not limit the scope of protection of the present invention.

[0040] In the embodiments and comparative examples of the present invention, the sources of the main raw materials are shown in Table 1 below. Unless otherwise specified, other raw materials and reagents were purchased from commercial sources:

[0041] Table 1 Raw material source information

[0042] Raw materials / specifications factory Specification 1,3-Butadiene Wanhua Chemical >99% Styrene Wanhua Chemical >99.5% Acrylonitrile Aladdin >99.5% SAN resin Chi Mei Industrial PN128 <![CDATA[MgSO4]]> Alpha Elsa 99.98%

[0043] In each embodiment and comparative example of the present invention, the main equipment used is shown in Table 2 below:

[0044] Table 2 Main equipment information

[0045]

[0046]

[0047] In each embodiment and comparative example of the present invention, the product performance test parameters and corresponding test methods are as follows:

[0048] Latex particle size: 1 g of latex was mixed with 100 g of deionized water, and the average particle size was measured using a Malvern Mastersizer laser particle size analyzer according to the dynamic laser scattering method;

[0049] Gel rate: The rubber polymer is coagulated with dilute acid, washed with deionized water, dried in a vacuum oven at 60°C for 24 hours, and the resulting gel blocks are cut into pieces with scissors. 1g of the gel block fragments are immersed in 100g of toluene and stored at room temperature for 48 hours. The resulting solution is separated into sol and gel (insoluble matter). The separated gel part is dried in an oven at 85°C for 6 hours, the weight of the dried gel is tested, and the gel content is calculated using the following formula;

[0050] Gel ratio = gel weight after drying / sample weight * 100%

[0051] Electroplating and coating adhesion test: After the prepared ABS resin is dried, it is molded into 3mm*15mm*10mm sheets by an injection molding machine and electroplated at Yantai Sanhuan Electroplating Factory. After electroplating, the parts are cut according to ASTM B533 and then tested for coating adhesion using a universal testing machine;

[0052] TEM electron microscope test: After the prepared ABS resin is injection molded, the surface slices are cut and dyed by osmium tetroxide fumigation. After cleaning, the dispersion morphology of rubber particles in the resin is observed by electron microscope.

[0053] Example 1

[0054] Polybutadiene latex preparation:

[0055] (1) 9 g of potassium oleate, 11 g of potassium disproportionate rosin acid, 1000 g of butadiene, 6 g of potassium carbonate, 7 g of tert-dodecyl mercaptan (TDM), and 1000 g of deionized water were added to a reactor, heated to 65° C., and 2.5 g of potassium persulfate was added to initiate an emulsion polymerization reaction. After reacting for 12 h, the butadiene conversion rate in the reactor was 91.5%. The reaction was stopped, and unreacted butadiene was removed by vacuum flash evaporation at 50° C. and 8 KPaA until the residual butadiene content was 736 ppm, thereby obtaining a polybutadiene latex emulsion with a latex particle size of 283 nm.

[0056] (2) The reactor was heated to 72° C. and maintained at this temperature for 2 h to obtain a polybutadiene latex emulsion with a gel fraction of 86.5%.

[0057] Graft latex preparation:

[0058] Take 1000g of polybutadiene latex emulsion, add 0.01g of FeSO4 thereto, stir evenly, gradually heat the reaction system to 70°C, gradually add 1g of cumene hydroperoxide, 117g of styrene, 46g of acrylonitrile, 2g of tert-dodecyl mercaptan, 3g of potassium oleate and 100g of deionized water thereto, the continuous addition time is 3h, after the addition is completed, continue to react for 3h, and obtain a grafted latex emulsion with a grafting rate of 40.5%;

[0059] Preparation of grafted rubber powder by coagulation / drying:

[0060] 1000 g of the grafted latex emulsion obtained above was added to a reaction kettle, heated to 95° C., 40 g of MgSO4 and 400 g of deionized water were gradually added thereto, the temperature was maintained, and the reaction was uniformly stirred for 1 hour. The obtained condensed emulsion was filtered using a 200-mesh stainless steel filter cloth to obtain a grafted powder containing 32% moisture, which was dried in a vacuum drum dryer at 60° C. and 2 KPaA for 4 hours to obtain a grafted powder with a moisture content of 0.73%;

[0061] Preparation of electroplating ABS resin by mixing:

[0062] A twin-screw extruder was used at 20 rpm and 200° C. Chi Mei PN128 was used as the blending SAN phase, and the blending was performed at a blending ratio of PN128: the above grafted powder = 70 / 30. After cooling and granulation, the electroplated ABS resin product was obtained.

[0063] The prepared resins were made into sheets at injection molding rates of 5 ccm / s, 10 ccm / s, and 30 ccm / s, respectively. The prepared resin sheets were electroplated at Sanhuan Electroplating Factory, and the coating bonding strengths tested according to ASTM B533 were 12.6 N / cm, 11.7 N / cm, and 10.3 N / cm, respectively.

[0064] The surface of the sheet prepared at an injection rate of 30 ccm / s was frozen and sliced, and then stained with osmium tetroxide and observed by TEM. Figure 1 .

[0065] Example 2

[0066] Polybutadiene latex preparation:

[0067] (1) 8 g of potassium stearate, 8 g of potassium disproportionate rosin acid, 1000 g of butadiene, 5 g of potassium phosphate, 3.5 g of n-dodecyl mercaptan and 700 g of deionized water were added to a reaction kettle, heated to 70° C., 2.1 g of sodium persulfate was added to initiate emulsion polymerization, and after 10 h of reaction, the butadiene conversion rate in the kettle was 92.8%. The reaction was stopped, and unreacted butadiene was removed by vacuum flash evaporation at 50° C. and 8 KPaA until the residual butadiene content was 817 ppm, thereby obtaining a polybutadiene latex emulsion with a latex particle size of 331 nm.

[0068] (2) The reactor was heated to 65° C. and the temperature was maintained for 1 h to obtain a polybutadiene latex emulsion with a gel fraction of 89.1%.

[0069] The method of Example 1 was used to prepare grafted latex, grafted rubber powder and electroplated ABS resin.

[0070] The prepared resin was made into sheets at injection molding rates of 5 ccm / s, 10 ccm / s, and 30 ccm / s, respectively. The prepared resin sheets were electroplated at Sanhuan Electroplating Factory, and the coating bonding strengths tested according to ASTM B533 were 11.5 N / cm, 10.4 N / cm, and 9.8 N / cm, respectively.

[0071] Example 3

[0072] Polybutadiene latex preparation:

[0073] (1) 4 g of sodium dodecylbenzene sulfonate, 19 g of potassium linoleate, 1000 g of butadiene, 3 g of potassium sulfite, 5.2 g of n-octyl mercaptan and 1500 g of deionized water were added to a reaction kettle, heated to 62° C., 3 g of tert-butyl hydroperoxide was added to initiate an emulsion polymerization reaction, and after 15 h of reaction, the butadiene conversion rate in the kettle was 94.6%. The reaction was stopped, and unreacted butadiene was removed by vacuum flash evaporation at 50° C. and 8 KPaA until the residual butadiene content was 854 ppm, thereby obtaining a polybutadiene latex emulsion with a latex particle size of 235 nm.

[0074] (2) The reactor was heated to 78° C. and maintained at this temperature for 2 h to obtain a polybutadiene latex emulsion with a gel fraction of 92.3%.

[0075] The method of Example 1 was used to prepare grafted latex, grafted rubber powder and electroplated ABS resin.

[0076] The prepared resins were made into sheets at injection molding rates of 5 ccm / s, 10 ccm / s, and 30 ccm / s, respectively. The prepared resin sheets were electroplated at Sanhuan Electroplating Factory, and the coating bonding strengths tested according to ASTM B533 were 13.2 N / cm, 12.8 N / cm, and 12.2 N / cm, respectively.

[0077] Comparative Example 1

[0078] Compared with the embodiment, the difference is that the S3 heat treatment step is not included.

[0079] Polybutadiene latex preparation:

[0080] 0.9 parts of potassium oleate, 1.1 parts of potassium disproportionate rosin acid, 100 parts of butadiene, 0.6 parts of potassium carbonate, 0.7 parts of tert-dodecyl mercaptan (TDM), and 100 parts of deionized water were added to a reactor, heated to 65°C, and 0.25 parts of potassium persulfate were added to initiate emulsion polymerization. After 12 hours of reaction, the butadiene conversion rate in the reactor was 91.9%, and the reaction was stopped. Unreacted butadiene was removed by vacuum flash evaporation at 50°C and 8KPaA until the residual butadiene content was 789ppm, and a polybutadiene latex emulsion with a latex particle size of 291nm was obtained. The gel fraction was tested to be 80.2%.

[0081] The method of Example 1 was used to prepare grafted latex, grafted rubber powder and electroplated ABS resin.

[0082] The prepared resin was made into sheets at injection molding rates of 5 ccm / s, 10 ccm / s, and 30 ccm / s, respectively. The prepared resin sheets were electroplated at Sanhuan Electroplating Factory, and the coating bonding strengths tested according to ASTM B533 were 10.2 N / cm, 6.9 N / cm, and 3.7 N / cm, respectively.

[0083] The surface of the sheet prepared at an injection rate of 30 ccm / s was frozen and sliced, and then stained with osmium tetroxide and observed by TEM. Figure 2 .

[0084] It can be seen from the above that, by using the ABS resin prepared by the present invention, the rubber particles on the surface of the product maintain a good spherical morphology at a high injection rate, so that it has better coating bonding strength during the resin electroplating process.

[0085] Those skilled in the art will appreciate that, based on the teachings of this specification, some modifications or adjustments may be made to the present invention, and these modifications or adjustments should also be within the scope defined by the claims of the present invention.

Claims

1. A method for preparing polybutadiene latex, characterized in that: The method comprises the following steps: S1: adding water, emulsifier, butadiene, electrolyte, chain transfer agent and initiator into a reactor to carry out emulsion polymerization; S2: When the polymerization reaction reaches the target conversion rate, unreacted butadiene is removed to obtain polybutadiene latex; S3: heat-treating the polybutadiene latex emulsion to increase the gel fraction of the latex and obtain the target polybutadiene latex emulsion; Among them, the latex gel rate in S3 is increased to 85%-95%.

2. The preparation method according to claim 1, characterized in that: The mass ratio of each component used in the polybutadiene latex described in S1 is as follows: Preferably, the emulsifier is selected from C12-C20 carboxylates and / or sulfonates, preferably one or more of disproportionated rosin acid, oleic acid, linoleic acid, stearic acid and potassium or sodium salt of dodecylbenzenesulfonic acid; Preferably, the electrolyte is selected from metal salts of Group IA metals, preferably one or more of sodium carbonate, potassium carbonate, potassium phosphate, and sodium sulfite; Preferably, the chain transfer agent is selected from C8-C18 mercaptans, preferably one or more of tert-dodecyl mercaptan, n-dodecyl mercaptan, n-octyl mercaptan and n-octadecyl mercaptan; Preferably, the initiator is selected from persulfates and / or organic peroxides, preferably one or more of sodium persulfate, potassium persulfate, cumene hydroperoxide, and tert-butyl hydroperoxide; and / or, the polymerization reaction temperature in S1 is 50°C-85°C, preferably 60°C-75°C; And / or, the particle size of the polybutadiene latex prepared in S1 is 100-500 nm, preferably 200-400 nm.

3. The preparation method according to claim 1, characterized in that: The method for removing unreacted butadiene described in S2 can adopt flash distillation and / or stripping; and / or, in S2, when the butadiene conversion rate of the polymerization reaction reaches 85-97%, preferably 90-95%, removing unreacted butadiene; Preferably, the unreacted butadiene content is removed to a mass content of <2000 ppm.

4. The preparation method according to claim 1, characterized in that: The temperature of the heat treatment in S3 is 50-90°C, preferably 60-80°C.

5. A polybutadiene latex, wherein the latex is prepared by the method according to any one of claims 1 to 4, and the gel fraction of the latex is 85% to 95%.

6. Use of a polybutadiene latex, wherein the latex is prepared by the method according to any one of claims 1 to 4, or is the polybutadiene latex according to claim 5, and the polybutadiene latex is used to prepare ABS resin.

7. An ABS resin, wherein the raw material of the resin is the polybutadiene latex prepared by the method according to any one of claims 1 to 4, or the raw material of the resin is the polybutadiene latex according to claim 5.

8. Use of ABS resin, wherein the raw material of the resin is the polybutadiene latex prepared by the method according to any one of claims 1 to 4, or the raw material of the resin is the polybutadiene latex according to claim 5, and the ABS resin is used for electroplating ABS resin.

Citation Information

Patent Citations

  • Rubber modified polystyrene resin for electroplating

    CN102653582A

  • Electroplating ABS (Acrylonitrile Butadiene Styrene) resin with high binding force and preparation method thereof

    CN103342864A

  • Thermoplastic resin composition, method for manufacturing same, and metal-plated molded product manufactured from same

    CN111372990A

  • Method for preparing thermoplastic resin composition with remarkable surface clearness and gloss

    CN104768988A

  • Transparent ABS resin and transparent ABS resin composition

    CN105008406A

Cited By

  • High-heat-resistance electroplating-grade bulk ABS (acrylonitrile-butadiene-styrene) resin and preparation method thereof

    CN121021765A